영어교육전공 대학생의 교양영어 교육에 대한 연구 - 김지은(Ji-Eun Kim); 최용훈(Young Hun Choi) (한국콘텐츠학회 논문지, 19(8), 2019)
This study aims to suggest more efficient ways of teaching English more related to but distinct from major English, based on the needs and awareness of the students of English Education Department. For this, interviews and surveys have been carried out targeting some English Education majors. The results show that the satisfaction level of students is relatively low, marking around the score '3'. While the satisfaction level about classroom environment including the multi-media equipment, and professors' teaching ability, quality and methods is higher compared with other factors, the improvement of English skills and interest-causing levels are lower on average. Besides, this study also includes the surveys on the needs of students for various teaching programs, differentiated classes and qualified instructors. Based on the results, this study makes three suggestions as follows; (1) the opening of some specific English classes for English-education majors (2) the development of English-conversation classes related to English-education majors (3) the development of communication-centered English reading based on English literature. 본 연구는 사범대학 영어교육과에 재학 중인 학생들의 교양영어에 대한 인식과 요구를 바탕으로, 전공에 특화되나 전공 교육과는 차별화된 좀 더 효과적인 교양 영어교육에 대한 제언을 하고자 하는 것을 목적으로 한다. 이를 위하여 영어교육과에 재학 중인 학생들을 대상으로 영어교양 교육의 인식과 요구와 관련된 설문과 인터뷰를 수행하였다. 설문 결과, 현 교양영어에 대한 영어교육과 학생들의 만족도는 전체적으로 3점대로 높지는 않았다. '멀티미디어 시설 등 강의실 환경'에 대한 만족도나 교수진의 전문성, 자질, 교수방법'은 타 항목에 비해서 평균 점수가 비교적 높았으나 '영어실력 향상의 정도'나 '흥미유발 정도'에 대한 항목 가장 낮은 평균점수를 보였다. 이 외에도 본 연구에서 수행한 교양영어 프로그램에 대한 요구와 수준별 수업에 대한 요구, 교수자에 대한 요구 결과를 바탕으로 영어교육 전공자들을 위한 교양영어 교육을 위하여 제안은 다음과 같다. 첫째, 영어 교육 전공자들을 위한 전공특화 교양영어선택 과목을 개설한다. 둘째, 전공과 연계된 교양영어 회화 과목을 개발한다. 또한 영문학을 바탕으로 한 의사소통중심 교양 독해수업을 개발한다.